Implementation of Coastal Ecotourism Management Policy in Tanjungpinang City Case Study of Mangrove Area - Fatmo, Siyardi; Samin, Rumzi; Akhyary, Edy (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Mangrove ecotourism in Tanjungpinang City is a very potential sector to support sustainable development, especially in preserving mangrove ecosystems and improving the welfare of local communities. The background of this study focuses on the importance of effective mangrove ecotourism management amidst various environmental threats, such as deforestation and lack of supporting infrastructure. The purpose of this study is to analyze the implementation of mangrove ecotourism management policies in Tanjungpinang and identify obstacles and opportunities that arise in the process. The method used in this study is descriptive qualitative, with data collection through in-depth interviews, field observations, and analysis of related policy documents. This study also uses a policy analysis approach to evaluate the implementation of local government policies. The results of the study indicate that although there are policies that support mangrove ecotourism management, their implementation is not optimal. The main obstacles faced include low local community participation, lack of funding, and limited environmentally friendly tourism infrastructure. In addition, supervision of activities that damage the ecosystem, such as illegal logging, is still ineffective. The conclusion of this study is that mangrove ecotourism management in Tanjungpinang requires improvements in terms of community participation, adequate funding, and strengthening regulations and supervision. Collaborative efforts between government, communities and the private sector are key to success in creating sustainable ecotourism and providing economic and environmental benefits to local communities.